Expression and Function of IL-33/ST2 Axis in the Central Nervous System Under Normal and Diseased Conditions - Fairlie-Clarke, Karen; Barbour, Mark; Wilson, Chelsey; Hridi, Shehla U.; Allan, Debbie; Jiang, Hui-Rong (Frontiers in Immunology, 2018)
Interleukin-33 (IL-33) is a well-recognised immunomodulatory cytokine which plays critical roles in tissue function and immune-mediated diseases. The abundant expression of IL-33 in brain and spinal cord prompted many scientists to explore its unique role in the central nervous system (CNS) under physiological and pathological conditions. Indeed emerging evidence from over a decade’s research suggests that IL-33 acts as one of the key molecular signalling cues coordinating the network between the immune and CNS systems, particularly during the development of neurological diseases. Here, we highlight the recent advances in our knowledge regarding the distribution and cellular localisation of IL-33 and its receptor ST2 in specific CNS regions, and more importantly the key roles IL-33/ST2 signalling pathway play in CNS function under normal and diseased conditions.